Alterations of Candidatus Liberibacter asiaticus-Associated Microbiota Decrease Survival of Ca. L. asiaticus in in vitro Assays - Fujiwara, Kazuki; Iwanami, Toru; Fujikawa, Takashi (Frontiers in Microbiology, 2018)
Phloem-inhabiting bacterial phytopathogens often have smaller genomes than other bacterial phytopathogens. It is thought that they depend on both other phloem microbiota and phloem nutrients for colonization of the host. However, the mechanism underlying associations between phloem-inhabiting phytopathogens and other phloem microbiota are poorly understood. Here, we demonstrate that the survival of Candidatus Liberibacter asiaticus (CLas), a cause of huanglongbing (citrus greening disease), depends on interplay with a specific subset of CLas-associated microbiota. CLas was not susceptible to oxytetracycline in vitro. However, oxytetracycline treatment eliminated a particular sub-community dominated by the Comamonadaceae, Flavobacteriaceae, Microbacteriaceae, and Pseudomonadaceae, decreasing CLas survival. We speculate that CLas uses ecological services derived from CLas-associated microbiota to colonize the host and to construct a pathogen-associated community that stimulates disease development.